Better Together: Supporting Perinatal and Infant Mental Health Services in the City of Wanneroo and the City of Joondalup - Kiely, Daniel; Fitzgerald, Hiriam; Matacz, Rochelle; Priddis, Lynn; Bayes, Sara; Barratt-Pugh, Caroline; Pooley, Julie Ann (2019)
The project maps how services in the cities of Wanneroo/Joondalup interact to enhance the quality of perinatal and infant mental health services for the community. Service providers were invited to work with the research team over 12 months to design, implement and evaluate the network of services that families with infants and young children access. We used an action research method to analyse the system as well as the client experiences. Together with the community, the project worked to think about and improve the system responsiveness to the social wellbeing and mental health needs of families with infants and young children, from both prevention and intervention perspectives. This was done through capturing factors that help and that hinder networking and through building workforce development plans, training pathways and resources to increase the awareness of perinatal and infant mental health, referral pathways, good practice and interventions.